2010
DOI: 10.2320/matertrans.l-mg200952
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Strain-Induced Boundary Migration as Evaluated by the Crystal Rotation Axis Method in (001) [100] and (112) [11\\bar1] Aluminum Bicrystal Deformed by Plane-Strain Compression

Abstract: An aluminum bicrystal with (001) [100] and (112) [11 " 1 1] orientation was deformed by plain-strain compression to a strain of 0.34. The types of slip systems responsible for producing crystal rotations relative to the initial orientations were clarified by the crystal rotation axis method. In the (001) [100] crystal, an affected zone developed along the grain boundary, which revealed a variety of slip systems in operation; the operation of some of these systems could be predicted from the Schmid factor wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…3) for both steels [23,24]. This suggests that the strain-induced boundary migration (SIBM) mechanism was dominant during recrystallisation at 1200°C, as reported by several researchers [23,25,26]. A characteristic feature of this mechanism is that the new grains have similar orientations to the old grains from which they have grown [27].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…3) for both steels [23,24]. This suggests that the strain-induced boundary migration (SIBM) mechanism was dominant during recrystallisation at 1200°C, as reported by several researchers [23,25,26]. A characteristic feature of this mechanism is that the new grains have similar orientations to the old grains from which they have grown [27].…”
Section: Discussionmentioning
confidence: 54%
“…5), but they are different from the recrystallisation textures at 1100°C (Fig. 3) for both steels [23,24]. This suggests that the strain-induced boundary migration (SIBM) mechanism was dominant during recrystallisation at 1200°C, as reported by several researchers [23,25,26].…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, the formation of nanoscale Fe 3 C within the DIFT also suggests a massive transformation for the DIFT. Ti steels and showed that the recrystallisation texture (after 10s at 1200°C) was closely related to the deformation texture after roughing deformation at 850°C for both steels, but different from the recrystallization textures after heat treatment at 1100°C for 30s [43]. This suggests that the strain-induced boundary migration (SIBM) mechanism was dominant during recrystallisation, as reported by several researchers [43][44][45].…”
Section: Size and Morphology Of Prior Austenite Grain Sizementioning
confidence: 65%
“…Ti steels and showed that the recrystallisation texture (after 10s at 1200°C) was closely related to the deformation texture after roughing deformation at 850°C for both steels, but different from the recrystallization textures after heat treatment at 1100°C for 30s [43]. This suggests that the strain-induced boundary migration (SIBM) mechanism was dominant during recrystallisation, as reported by several researchers [43][44][45]. The SIBM would have probably left irregular grain boundaries, with serrations that could act as preferential sites for DIFT.…”
Section: Size and Morphology Of Prior Austenite Grain Sizementioning
confidence: 89%
“…where b s and n s are the slip direction and slip plane normal, respectively, for a given slip system, s. The Taylor axes as well as the Schmid factors of the 12 slip systems in grain ''B'' and grain ''F'' are given in Table 3. Due to the reaction stresses [33] imposed by the channel die, the potential active slip systems are b1, b2, b3, d2, and d3 in grain B and a2, b1, b3, and d2 in grain F. The practically active slip systems can be estimated based on the crystal rotation relative to the initial orientation by matching the Taylor axis for a given combination of slip systems to the experimentally measured lattice rotation axis [22,34,35]. Figure 7a gives the positions of the \112[, \110[, and \111[ axes in the crystal coordinate system, where the traces of {111} slip planes and {110} planes are drawn as big black circles.…”
Section: Slip System Analysismentioning
confidence: 99%